Evaluation of BRCAPRO Risk Assessment Model in Patients with Ductal Carcinoma In situ Who Underwent Clinical BRCA Genetic Testing - Elsayegh, Nisreen; Barrera, Angelica M. Gutierrez; Muse, Kimberly I.; Lin, Heather; Kuerer, Henry M.; Helm, Monica; Litton, Jennifer K.; Arun, Banu K. (Frontiers in Genetics, 2016)
The authors retrospectively aimed to determine which of the following 3 scenarios, related to DCIS entry into BRCAPRO, predicted BRCA mutation status more accurately: 1) DCIS as an invasive breast cancer (IBC) entered using the actual age of diagnosis, 2) DCIS as IBC entered with 10 years added to the actual age of diagnosis, and 3) DCIS entered as no cancer. Of the 85 DCIS patients included in the study, 19% (n= 16) tested positive for a BRCA mutation and 81% (n= 69) tested negative. DCIS patients who tested positive for a BRCA mutation had a higher BRCAPRO risk estimation (34.61%) than patients who tested negative (11.4%) when DCIS was entered at the actual age of diagnosis. When DCIS was entered with 10 years added to the actual age at diagnosis, the BRCAPRO estimate was still higher amongst BRCA positive patients (25.4%) than BRCA negative patients (7.1%). When DCIS was entered as no cancer, the BRCAPRO estimate remained higher among BRCA positive patients (2.56%) than BRCA negative patents (1.98%). In terms of accuracy of BRCA positivity, there was no statistically significant difference between DCIS at age at diagnosis, DCIS at 10 years later than age at diagnosis, and DCIS entered as no cancer (AUC= 0.77, 0.784, 0.75 respectively: p = 0.60). Our results indicate that regardless of entry approach into BRCAPRO, there were no significant differences in predicting BRCA mutation in patients with DCIS.